2010
DOI: 10.1007/s00234-010-0735-0
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular coil embolization of very small intracranial aneurysms

Abstract: Coil embolization of very small aneurysms may be technically feasible with favorable clinical/angiographic outcomes and relatively low recanalization rate during 6 months or more follow-up period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 20 publications
3
40
0
Order By: Relevance
“…T o achieve complete coil occlusion of an intracranial aneurysm, a stable microcatheter position is the single most important factor (2,5). A well-designed shape for the microcatheter is crucial in achieving this occlusion.…”
Section: Introductionmentioning
confidence: 99%
“…T o achieve complete coil occlusion of an intracranial aneurysm, a stable microcatheter position is the single most important factor (2,5). A well-designed shape for the microcatheter is crucial in achieving this occlusion.…”
Section: Introductionmentioning
confidence: 99%
“…Several series have reported good results with coiling of very small ruptured aneurysms (≤3 mm) [7,8]. In other series, even smaller ruptured aneurysms (≤2 mm) have been treated by coiling, including Gil et al's series of 4 patients [9] and Gupta et al's [10] series of 7 patients, both with good outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…In another patient, a residual wide-neck carotid terminus aneurysm was clipped after 9 months from the ictus to offer definitive treatment following stabilization by coiling. Despite the good aneurysm occlusion rates reported [8,10], we continue to advocate close follow-up for recanalization in this small and select patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Hwang et al [21] reported endovascular treatment of 43 very small aneurysms (23 ruptured, 20 unruptured) in 38 patients. There were 5 incidents of thrombosis (12%) and 1 procedural rupture (2%), but there was no definite adverse effect on clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%